2016
DOI: 10.1149/2.0091613jes
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Carbon Cloth for Supercapacitors Prepared via a Hydrothermal Process

Abstract: This paper reports a facile means of fabricating nitrogen-doped carbon cloth (CC) via a hydrothermal process in the presence of hydrazine and ammonia. The resulting N-doped CC can be used directly as an electrode for a supercapacitor, requiring no polymeric binder or current collector. X-ray photoelectron spectroscopy (XPS) revealed that the surface of oxidized CC was nitrogen-doped concurrently with reduction; in other words, the oxygen-containing groups were replaced with nitrogen species of different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…As mentioned above, the reduction process has strong influence on the electrochemical activity of the chemically treated carbon fiber materials. By using the reducing agent of hydrazine and ammonia at 160 °C, Nakayama et al . found that nitrogen was doped into the carbon matrix (N‐CC), and the content of nitrogen was evaluated to be 8.8 at%.…”
Section: Modification and Improvement Of Carbon‐fiber Materials Electrmentioning
confidence: 99%
“…As mentioned above, the reduction process has strong influence on the electrochemical activity of the chemically treated carbon fiber materials. By using the reducing agent of hydrazine and ammonia at 160 °C, Nakayama et al . found that nitrogen was doped into the carbon matrix (N‐CC), and the content of nitrogen was evaluated to be 8.8 at%.…”
Section: Modification and Improvement Of Carbon‐fiber Materials Electrmentioning
confidence: 99%
“…The use of organic wastes and biomass for manufacturing activated carbons is an efficient way and ecofriendly in nature. Attempts have been made to prepare differently activated carbons from biosources, such as dead leaves, bamboo, coconut shells, banana fibers, corn grains, sugar cane bagasse, cotton, human hair and catkins and their charge storage performance have also been studied [5,15,[22][23][24][25][26][27][28][29][30][31][32][33]. In some countries like India, after farming, the farmer burns the waste biomass, which causes huge air pollution by releasing CO and CO 2 to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…These areal capacitances are several orders of magnitude of commercially available carbon fiber cloth with a very low areal capacitance 43 (only 13 mF cm −2 at 1 mA cm −2 ) 44 . The areal capacitance C a value of 1846 mF cm −2 (at 1 mA cm −2 ) is more than twice of that for molten-NaNH 2 activated carbon cloth (744.5 mF cm −2 at 1 mA cm −2 ) 45 , ten times of that for N-doped carbon nanotubes (180 mF cm −2 at 0.5 mA cm −2 ) 46 and 14 times of that for N-doped carbon cloth (136 mF cm −2 at 0.5 mA cm −2 ) 47 . This implies that the enhanced capacitance is mainly attributed to the significant contribution of pseudocapacitive Fe 2 O 3 nanobelt arrays.…”
Section: Discussionmentioning
confidence: 85%
“…Also, this value is higher than three times of those for Fe 2 O 3 nanorods@graphene foam on Ni foam (572 mF cm −2 ) 49 , Fe 2 O 3 nanorods@NiO nanosheets on carbon cloth (557 mF cm −2 ) 15 , and Fe 2 O 3 nanoparticles@graphene foam-CNT (470.5 mF cm −2 ) 50 . The data for the performance comparison are shown in Table S1 15,27,[44][45][46][47][48][49][50] .…”
Section: Discussionmentioning
confidence: 99%